METHOD TO INVESTIGATE FICTIONAL ENTITIES: A CASE OF ISHINOMORI SHOTARO’S “KAMENRIDER BLACK” TV SERIES IN INDONESIA - Rizki Musthafa Arisun (LINGUA : JURNAL ILMIAH, 2018)
This article reports an experiment to pursue appropriate observation method on fictional entities inside popular culture products from Japan: two dimensional characters, fictional characters in a movie. Previous research showed how Indonesian popular culture producers being empowered in production, as fictional entities involved, such as “Hatsune Miku” (HM), a virtual singer persona. This article focused on older cases where media Japan travelled to Indonesia. Back in 1989, a TV action serial "Kamen Rider Black/　Ksatria Baja Hitam" (KRB/KBH) from Japan, was broadcasted by Indonesian local television station RCTI, and dubbed in Indonesian language. The experiment on finding appropriate observation method is conducted by constructing frameworks, imagined as ‘dissecting’ fictional entities into smaller observable parts. The purpose of this paper is to map methods to examine the role of non-human entities under transnational media by evaluating through early stage experiment.